Trapped by scandal - Feather, Jane (Pocket Books, 2015)
Lady Hero Fanshawe has chafed at society dictates since the death of her fiancé taught her that joy can be fleeting. When her brother disappears in Paris at the height of the Terror, she has no hesitation in disguising herself as a boy and risking her life to find him--or in joining forces with a chance-met ally, the enigmatic William Ducasse, Viscount St. Aubrey. And she has no regrets in indulging in a passionate affair with the dangerously handsome stranger, in the shadow of the guillotine.